2021
DOI: 10.3906/sag-2010-27
|View full text |Cite
|
Sign up to set email alerts
|

Clinical predictors of drug-resistant epilepsy in children

Abstract: Background/Aim: In up to 20% of epilepsy patients, seizures may not be controlled despite the use of antiepileptic drugs, either singly or in combination. These individuals are considered to have drug resistant epilepsy. Drug resistant epilepsy is usually associated with intellectual disability, psychiatric comorbidity, physical injury, sudden unexpected death, and low life quality. Early detection and prediction of drug resistant epilepsy is essential in determining the patient's most appropriate treatment op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 14 publications
2
13
1
Order By: Relevance
“…We found abnormal findings of interictal EEG monitoring were associated with DRE among PTE patients, especially the presence of epileptiform discharges. Previous studies also reported that focal epileptiform activity, 42 focal slowing, asymmetric spike–wave discharges, 42 and EEG with generalized epileptiform activity (primarily poly‐spikes) 31 were poor prognostic factors for epilepsy. Therefore, we believe that EEG monitoring, even routine interval EEG monitoring, is of great value in assessing the outcome of PTE.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…We found abnormal findings of interictal EEG monitoring were associated with DRE among PTE patients, especially the presence of epileptiform discharges. Previous studies also reported that focal epileptiform activity, 42 focal slowing, asymmetric spike–wave discharges, 42 and EEG with generalized epileptiform activity (primarily poly‐spikes) 31 were poor prognostic factors for epilepsy. Therefore, we believe that EEG monitoring, even routine interval EEG monitoring, is of great value in assessing the outcome of PTE.…”
Section: Discussionmentioning
confidence: 84%
“…According to a meta-analysis published by Kalilani et al 42 and EEG with generalized epileptiform activity (primarily poly-spikes) 31 were poor prognostic factors for epilepsy.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Yilmaz and colleagues [ 30 ] reported that Patients with drug-resistant epilepsy are more likely to experience mixed seizures than drug-responsive patients, who are more likely to experience generalized seizures. Similarly, a retrospective study showed that mixed seizure is an independent risk factor for drug-resistant epilepsy in childhood [ 31 ]. Chawla and colleagues [ 32 ] discovered that generalized tonic seizure was the most prevalent type in the drug-resistant epilepsy group.…”
Section: Discussionmentioning
confidence: 99%